Writing great speeches : professional techniques you can use - Perlman, Alan M. (Boston : Allyn and Bacon, 1998)
This series represents the accumulated wisdom of experts in various speech -related fields. the series covers the spectrum of speaking scenarios: writing for the ear, using storytelling and humor, customizing particular topics for various audiences, motivating people to action, using technology for presentation and other important topics.
Includes bibliographical references.
nmn, 13/07/18
Loans
Keywords: Speech writing; Public speaking